Strategies to increase the quantum yield: Luminescent methoxylated imidazo[1, 5-a]pyridines. (August 2021) - Volpi, G.; Garino, C.; Fresta, E.; Casamassa, E.; Giordano, M.; Barolo, C.; Viscardi, G.
Abstract: A series of methoxylated imidazo[1, 5- a ]pyridines is presented and their optical and electrochemical properties investigated and interpreted on the basis of density functional theory calculations. The photophysical properties are discussed in relation to the chemical structure. The key role of the 1, 3 substitutions on the imidazo[1, 5- a ]pyridine nucleus on rotational barriers and on frontier molecular orbitals is discussed in relation to the experimental hyperchromic effect, photoemission quantum yield and electrochemical properties. Depending on the position of the introduced methoxy substituents on the imidazo[1, 5- a ]pyridine nucleus, we are able to tune the Stokes shift and to increase the emission quantum yield from 22% to 50%. Highlights: Luminescent methoxylated imidazo[1, 5- a ]pyridines. Structural modification to increase emission quantum yield. PES scan relating emission quantum yield and rotational energy barriers. Imidazo[1, 5- a ]pyridines electrochemistry and frontier molecular orbitals. Wide range of Stokes shift.